Exploring Indonesian Higher Education Neoliberalization: A Discourse on the Role of Accounting - Ali Djamhuri; Wiwik Hidajah Ekowati (Jurnal Ilmiah Akuntansi, 2023)
The neoliberalization of higher education has attracted academic debate and public interest. Though less known by the public, accounting terminologies play a prominent role in that process more particularly in sticking commercial values to the life of universities that eventually made universities far from their own original missions. Applying Critical Discourse Analysis (CDA), this study explores the neoliberalization of Indonesian higher education by questioning how it took place, what kind of linguistic terminologies or jargon are mostly used, and how accounting concepts, terminologies, and technologies take a role in it. This study found that accounting—through its concepts, jargon, and technologies—helped a lot in making the success of the neoliberalization of Indonesian higher education. Accounting notions like efficiency, productivity, effectiveness, accountability, transparency, and fairness take their cognitive and emotive roles in supporting highly competitive modes of academic life in universities so that the core of neoliberal ideology, that is competition, has been made to be more easily, scientifically, and psychologically justifiable for both individuals and society. Moreover, transactional and commercial motive-based behaviours as an impact of the more liberalized way of life, expand rapidly to become a standard way of acting both on and outside the campuses which accelerates the formation of a more individualistic and competitive Indonesian society. Bureaucratically, the university officials—from the lowest level such as the head of the department up to the Rectors—tend to be more sensitive to achieving a series of standardised, quantitative, technical, short-term, and pragmatic performance indicators dictated by national and international ranking agencies like Webometric than to deal with more ideal, educational, and long-term mission achievement.